IDENTIFIKASI SEKTOR PERTANIAN DALAM PENENTUAN SEKTOR UNGGULAN DI KABUPATEN PATI - Eka Dewi Nurjayanti (Universitas Wahid Hasyim, 2013)
Pati Regency is a regency that relies on agriculture as the sector that contributed greatly to the formation of GDRP. Accordingly, this research is needed to determine the sectors and subsectors basis, so that local development can be done optimally. The basic method used is descriptive method, while for determination of the area of research is purposive method. The data used are secondary data obtained from the BPS, Bappeda, and Department of Agriculture. Methods of data analysis involves determining GDRP 2012 constant prices, location quotient analysis, component of regional growth analysis, and leading sectors and sub-sectors analysis. The result of the data analysis showed that based on the average value of LQ, there are three base sectors, that are agriculture sector; electric, gas and clear water sector; and financial, ownership and busines services sector. During the years 2009-2012, the sub sectors which has always been a sub sector basis are able to meet the needs of the region itself can even export to other region are farm food corps sub-sector, non food crops sub-sector, forestry sub-sector, and fishery sub-sector. From the nine sectors of the economy, only the slow-growing agricultural sector, while the other eight sectors of the economy have rapid growth. Agricultural sector, minning and quarring sector, manufacturing industry sector, and construction sector are the sectors that have a competitive advantage with the same sectors in the other regions in Central Java Province. The fifth sub-sectors of agriculture has rapid growth. There are four leading sectors in Pati Regency, that are agriculture sector, minning and quarring sector, manufacturing industry sector, and construction sector. In the agricultural sub-sector, there are four sub-sectors that have potential as a leading sub sectors, namely farm food corps subsector, non food crops sub-sector, forestry sub-sector, and fishery sub-sector. Key words: component of regional growth, leading sectors and sub-sectors, Location Quotient.